PENGARUH DISIPLIN DAN MOTIVASI TERHADAP KUALITAS PELAYANAN PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH (BPPRD) KABUPATEN LAMPUNG UTARA - Reta Ramadayanti; Ani Heryani; Masayu Nila Juwita (e-JKPP, 2020)
The problems in this study are: (1) is the discipline of employees influence on the quality of service on the Board of Tax management and regional retribution  of the North Lampung Regency, (2) whether the motivation affects the quality of service At the board of Tax management and regional retribution  of North Lampung Regency, (3) is the discipline and motivation of officers simultaneously affect the quality of service on the Board of Tax management and regional retribution  Lampung Regency NorthThe research method used in this research is explanatory design which is an investigation of causality by means of basing on the observation of the influence that occurs, namely conducting research by taking samples from the population Using a questionnaire as a Data collector tool. Research population of 74 employees on the board of Tax Management and regional levy  of North Lampung Regency. While the sample is 74 people or a total sample. The research variables are discipline as free variables (X1) and employee motivation as free variables (X2) as well as service quality is variable bound (Y). The results showed that there was a significant influence both the discipline and the motivation of employees to the quality of service on the Board of Tax management and regional retribution  of North Lampung Regency, the greatest influence of variable-forming Employee discipline is the dimension of attendance, while the smallest dimension of employee discipline variables is the dimension of cooperation. While the dimension of the biggest variable motivation officers are internal motivation and the smallest is external motivation. Based on the results of the research, can be submitted findings from this research that the most influencing in the staff discipline on the Board of Tax Management and regional levy  of North Lampung District is the importance of improving education and Training by employees to be able to work more professionally.